Advances in Nanogels - Lin, Chien-Chi; Mauri, Emanuele; Rossi, Filippo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the last two decades, nanogels have emerged as very promising and versatile biomaterials suitable for a wide range of applications. Their features, such as large surface areas, the ability to hold molecules, flexibility in their size and their water-based formulations, have earned them great recognition as drug delivery systems for various in vivo applications, confirming their potential. On the other hand, because of their tuneable and versatile characteristics, nanogels have been investigated in recent years for applications in various fields other than biomedicine. In view of this variety of possible applications of nanogels, in this Special Issue, we extend our knowledge on the topic of their possible uses described in literature, taking stock of the state-of-the-art for all possible nanogel applications and their synthesis methods.